Evaluating urban quality of life: a comprehensive study of District 12, Ho Chi Minh City, Vietnam - Hoang , Thi Viet Ha; Nguyen , Thi Binh (Interacción y Perspectiva, 2024)
This study investigates the determinants of quality of life among residents of District 12 in Ho Chi Minh City. Employing exploratory factor analysis (EFA) and regression analysis, the research develops a model to evaluate the impact of various factors on the inhabitants’ living standards. The analysis identified five primary factors, ranked according to their influence: living conditions, education and training, health and healthcare services, life stability, employment and income, family and social relationships, and infrastructure. Based on these findings, the study suggests prioritized strategies aimed at enhancing the quality of life in District 12. These recommendations are tailored to address the specific needs and challenges identified through the research. The study contributes valuable insights into urban planning and policy-making, particularly in rapidly developing urban areas.